Analysıs Of Work Motıvatıon Through Rewards And Organızatıonal Clımate In Generatıon Z In Jakarta - Antonia Caesarly Santosa; I Gede Adiputra (Cita Konsultindo Research Center, 2023)
In this day and age, where most of the employees currently working in a company or organization are people who belong to generation Z. It is also necessary to pay attention to things such as what can motivate generation Z to work in Jakarta through rewards and organizational climate. The purpose of this research was to determine the effect of rewards and organizational climate on the work motivation of Generation Z in Jakarta. This research was also conducted by taking primary data by distributing questionnaires to employees belonging to generation Z in the city of Jakarta. The samples taken were 180 respondents who met the requirements and criteria with a purposive sampling technique and the data were analyzed using the SEM or Structural Equation Modeling method with a quantitative approach. Data is processed using SmartPLS software version 3.2.9. The results obtained in this study are that the independent variables, namely rewards and organizational climate, have a significant and positive influence on the work motivation of Generation Z in Jakarta. The results of this study are also encouraged to provide advice to all organizations or companies in the Jakarta area in dealing with employees who belong to generation Z in providing work motivation with rewards and organizational climate.